2022
DOI: 10.1111/1556-4029.15149
|View full text |Cite
|
Sign up to set email alerts
|

A TikTok “Benadryl Challenge” death—A case report and review of the literature

Abstract: TikTok™, a social media platform popular with teenagers and young adults, hosts a variety of short‐form user videos with durations from 15 s to 10 min. Among these videos are potentially dangerous “challenges,” such as the “Skull Breaker” challenge and the “Benadryl” challenge. Benadryl (diphenhydramine) is an over‐the‐counter medication with potential for misuse in both suicidal and recreational purposes. We report the case of a 14‐year‐old girl who reportedly ingested an unknown amount of diphenhydramine whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Inexperienced adolescents are particularly vulnerable to this type of dynamic. While Tik Tok "challenges" are felt to be a distinct phenomenon (by both the authors of the paper, and by r/DPH users), there is potentially analogous harm in socially ordained medication use (Elkhazeen 2023).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Inexperienced adolescents are particularly vulnerable to this type of dynamic. While Tik Tok "challenges" are felt to be a distinct phenomenon (by both the authors of the paper, and by r/DPH users), there is potentially analogous harm in socially ordained medication use (Elkhazeen 2023).…”
Section: Discussionmentioning
confidence: 92%
“…Not only would such data be challenging to obtain through conventional methods, but recent events suggest that social media is an unparalleled source of substance misuse information, including emerging trends of misuse that quickly outpace public health efforts. In 2020, for example, a video on the social media platform TikTok encouraging ingestion of a high dose of Benadryl ("Benadryl Challenge") was implicated in hospitalizations and deaths (e.g., Elkhazeen et al, 2023), resulting in a drug safety report by the Food and Drug Administration (FDA, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have even demonstrated its efficacy in reducing preoperative anxiety, showcasing its potential for positive impact in healthcare settings [5]. However, recent reports have shed light on a concerning trend: the emergence of new types of injuries and burns stemming from the misuse of social media platforms and their content, particularly among vulnerable populations [1][2][3].…”
Section: Discussionmentioning
confidence: 99%
“…TikTok has been criticized for having inappropriate content that may result in not only misinformation and psychological effects but also addiction and serious injuries. Some dangerous viral trends such as the "Benadryl Challenge" and "Black-out Challenge" started on TikTok and led to the hospitalization and death of children [1][2][3]. It is crucial to draw the attention of medical staff to these new types of pathologies associated with the utilization of social networks.…”
Section: Introductionmentioning
confidence: 99%
“…Benadryl or diphenhydramine is a popular over-the-counter histamine and muscarinic receptor antagonist used to treat allergies [ 34 ]. Several cases of intoxication have been reported in relation to this challenge as well as a death case and a case of seizures, both in 14-year-old children who have ingested Benadryl to follow the trend [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%